2016
DOI: 10.1016/j.neuropharm.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of brain glucose uptake by cannabinoid CB2 receptors and its therapeutic potential in Alzheimer's disease

Abstract: Cannabinoid CB2 receptors (CB2Rs) are emerging as important therapeutic targets in brain disorders that typically involve neurometabolic alterations. We here addressed the possible role of CB2Rs in the regulation of glucose uptake in the mouse brain. To that aim, we have undertaken 1) measurement of (3)H-deoxyglucose uptake in cultured cortical astrocytes and neurons and in acute hippocampal slices; 2) real-time visualization of fluorescently labeled deoxyglucose uptake in superfused hippocampal slices; and 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 72 publications
2
30
0
1
Order By: Relevance
“…Likewise, AEA was reported to promote neurogenesis after Aβ‐induced neurotoxicity and reduce gliosis and cognitive decline in several models of neurodegenerative disease . AEA content in postmortem human midfrontal cortex was found to be inversely associated with Aβ42 peptide levels and to be reduced in the hippocampus of Tg mice . The trend towards a reduction of AEA and PEA brain levels in Tg mice appears, therefore, in partial agreement with the previously reported significant decrease .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Likewise, AEA was reported to promote neurogenesis after Aβ‐induced neurotoxicity and reduce gliosis and cognitive decline in several models of neurodegenerative disease . AEA content in postmortem human midfrontal cortex was found to be inversely associated with Aβ42 peptide levels and to be reduced in the hippocampus of Tg mice . The trend towards a reduction of AEA and PEA brain levels in Tg mice appears, therefore, in partial agreement with the previously reported significant decrease .…”
Section: Resultssupporting
confidence: 86%
“…AEA content in postmortem human midfrontal cortex was found to be inversely associated with Aβ42 peptide levels and to be reduced in the hippocampus of Tg mice . The trend towards a reduction of AEA and PEA brain levels in Tg mice appears, therefore, in partial agreement with the previously reported significant decrease . While the importance of appropriate levels of ω‐3 DHA (22:6), EPA (20:5), and ω‐9 oleic acid (18:1), and balanced proportion of phospholipids (PLP) for healthy ageing is well acknowledged, the involvement of EPEA and DHEA in neurodegenerative diseases is still poorly understood.…”
Section: Resultssupporting
confidence: 84%
“…The levels of AEA were reduced in the hippocampus of a mouse genetic model of AD (transgenic mice overexpressing amyloid precursor protein, APP) (TgAPP‐2576) (Kofalvi et al . ). The ECs acting through transient receptor potential cation channel subfamily V member 1 (TRPV1) were suggested to play a significant role in Aβ‐induced cognitive impairment in D3 receptor KO mice (Micale et al .…”
Section: Changes In the Endocannabinoid System In Neurodegenerative Dmentioning
confidence: 97%
“…For example, a recent study has reported the use of a cannabinoid receptor type 2 agonist to enhance CNS glucose uptake (131). Interventions targeting β-adrenoceptors, which induce glucose uptake and storage and breakdown of glycogen in astrocytes, also have promise to improve the supply of glucose and lactate to neurons and modify disease progression (132,133).…”
Section: Relevance To Alzheimer's Diseasementioning
confidence: 99%